Richard Neutra, 1892-1970 : survival through design - Lamprecht, Barbara Mac (Köln ; London : Taschen, 2009)
Born and raised in Vienna, Richard Neutra (1872-1970) came to America early in his career, settling in California. His influence on post-war architecture is undisputed, the sunny climate and rich landscape being particularly suited to his cool, sleek modern style. Neutra had a keen appreciation for the relationship between people and nature.
Includes bibliographical references and index.
Keywords: Neutra, Richard Joseph, -- 1892-1970 |x Criticism and interpretation; Architecture, Modern -- 20th century